Mitogenome diversity of Aedes (Stegomyia) albopictus: Detection of multiple introduction events in Portugal. - Líbia Zé-Zé; Vítor Borges; Hugo Costa Osório; Jorge Machado; João Paulo Gomes; Maria João Alves (PLoS Neglected Tropical Diseases, 2020)
Aedes albopictus, along with Ae. aegypti, are key arbovirus vectors that have been expanding their geographic range over the last decades. In 2017, Ae. albopictus was detected for the first time at two distinct locations in Portugal. In order to understand how the Ae. albopictus populations recently introduced in Portugal are genetically related and which is their likely route of invasion, we performed an integrative cytochrome C oxidase I gene (COI)- and mitogenome-based phylogeographic analysis of mosquitoes samples collected in Portugal in 2017 and 2018 in the context of the global Ae. albopictus diversity. COI-based analysis (31 partial sequences obtained from 83 mosquitoes) revealed five haplotypes (1 to 5), with haplotype 1 (which is widely distributed in temperate areas worldwide) being detected in both locations. Haplotypes 2 and 3 were exclusively found in Southern region (Algarve), while haplotype 4 and 5 were only detected in the North of Portugal (Penafiel, Oporto region). Subsequent high discriminatory analyses based on Ae. albopictus mitogenome (17 novel sequences) not only confirmed a high degree of genetic variability within and between populations at both geographic locations (compatible with the Ae. albopictus mosquito populations circulating in Europe), but also revealed two mitogenome mutational signatures not previously reported at worldwide level. While our results generally sustain the occurrence of multiple introduction events, fine mitogenome sequence inspection further indicates a possible Ae. albopictus migration within the country, from the Northern introduction locality to the Southern region. In summary, the observed scenario of high Ae. albopictus genetic diversity in Portugal, together with the detection of mosquitoes in successive years since 2017 in Algarve and Penafiel, points that both Ae. albopictus populations seem to be already locally established, as its presence has been reported for three consecutive years, raising the public health awareness for future mosquito-borne diseases outbreaks.